Interplay Between Thyroid Hormone Status and Pulmonary Hypertension in Graves’ Disease: Relevance of the Assessment in Thyrotoxic and Euthyroid Patients - Araruna, Larisse Vieira Mendes; Oliveira, Daniela Camargo de; Pereira, Mônica Corso; Moura Neto, Arnaldo; Tambascia, Marcos Antonio; Zantut-Wittmann, Denise Engelbrecht (Frontiers in Endocrinology, 2022)
Background: Graves' disease (GD) is the most common cause of hyperthyroidism and can cause cardiac changes, such as pulmonary hypertension. Methods: This is a prospective study in which we obtained demographic, clinical, laboratory data and characteristics of the GD, in addition to investigating cardiorespiratory function, focusing on the detection of pulmonary hypertension. Patients were separated in thyrotoxicosis and in euthyroidism groups. Ninety patients with GD of both sexes, over 18 years of age, were included. The cardiorespiratory assessment included an echocardiographic evaluation, questionnaire of specific symptoms, spirometry and six-minute walk test. Results: Hyperthyroid group included 42 patients (47.73%) and euthyroid group 46 patients (52.27%); 78 were women (86.67%). The prevalence of pulmonary hypertension between the hyperthyroidism (48.57%) and euthyroidism (29.41%) groups was not different. Free thyroxine levels (FT4) (OR 1.266), higher left atrium volume (OR 1.113) and right ventricle diameter were associated with pulmonary hypertension. A direct correlation between FT4 with forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1), as also an inverse correlation between initial oxygen saturation (SpO2) with diagnostic time and drop SpO2 with the ratio between the diastolic velocity E of the mitral flow and the diastolic velocity of the mitral ring (E/e’) were observed in the euthyroid group. An inverse correlation between FT4 levels with walked distance as % of predicted value, and a direct correlation between E/e' ratio and walked distance as % of predicted value were observed in the hyperthyroid group. Conclusion: We emphasize the importance of cardiorespiratory reassessment in GD, even after a long-term control of the thyrotoxic state, as we demonstrate that about 30% of these patients remain with PH and are subject to specific treatment.